Advancements in Managing Anthracycline-Induced Cardiotoxicity: Insights from Interventional Clinical Trials - Zhao M; Zhang X; Zhou D; Song J (Open Access Journal of Clinical Trials)
Mei Zhao,1 Xiaohong Zhang,1 Dongyang Zhou,2 Junxian Song3– 5 1Department of Pharmacy, Peking University People’s Hospital, Beijing, People’s Republic of China; 2Department of Metabolism, Digestion and Reproduction, Faculty of Medicine, Imperial College London, London, UK; 3Department of Cardiology, Peking University People’s Hospital, Beijing, People’s Republic of China; 4Beijing Key Laboratory of Early Prediction and Intervention of Acute Myocardial Infarction, Peking University People’s Hospital, Beijing, People’s Republic of China; 5Center for Cardiovascular Translational Research, Peking University People’s Hospital, Beijing, People’s Republic of ChinaCorrespondence: Junxian Song, Department of Cardiology, Peking University People’s Hospital, No. 11 Xizhimen South Street, Xicheng District, Beijing, 100044, People’s Republic of China, Email sjx221@163.comPurpose: Anthracycline-induced cardiotoxicity (AIC) is a significant complication in cancer treatment, impacting long-term health outcomes. This study aimed to evaluate interventional clinical trials targeting AIC and identify effective strategies.Methods: We reviewed clinical trials on AIC from International Clinical Trial Registration Platform (ICTRP), focusing on intervention strategies. We assessed the publication status and effectiveness of cardioprotective agents, monitoring techniques, and exercise interventions.Results: A total of 100 trials were identified, with 35% published. Most studies were conducted in the United States, China, and Italy, highlighting geographical disparities. Effective interventions included dexrazoxane for primary prevention, ACEI/ARB combination with β blockers for long-term cardioprotection. Advanced monitoring techniques, including global longitudinal strain (GLS)-guided echocardiography, cardiac magnetic resonance (CMR) and novel biomarkers (cfDNA, microRNA), showed promise in early AIC detection. Exercise interventions demonstrated significant cardiovascular benefits.Conclusion: Cardioprotective agents, early detection methods, and exercise interventions are key to managing AIC. Dexrazoxane and ACEI/ARB combination with β blockers are promising. Exercise interventions can improve cardiovascular health and reduce AIC risk. Larger trials with long-term follow-up are essential for refining these strategies.Keywords: anthracycline-induced cardiotoxicity, clinical trials, cardiovascular toxicity, cancer therapy safety